The doctor dissected : a cultural autopsy of the Burke and Hare murders - McCracken-Flesher, Caroline (Oxford University Press, 2012)
A series of bizarre disappearances filled the citizens of early nineteenth-century Scotland with terror. When the perpetrators were finally apprehended in 1828, their motive roiled the nation: William Burke and William Hare had murdered for profit. The cadavers supplied a ready payout, courtesy of Dr. Robert Knox, who was desperate for anatomical subjects. Nearly two hundred years later, these scandalous murders continue to fire imagination in Scotland and beyond. From the start, the sensational events provoked artists and writers. While Sir Walter Scott resisted public comment, his correspond.